Confined biofilm culture in microfluidic channels for the investigation of biofilm response to sudden temperature changes - Lim, Siang Joo (2015)
Microfluidics – the manipulation and analysis of minute volumes of fluid – has emerged as a powerful technology with many established and relevant applications in various fields, one of which being biofilm development in bacteriology. Owing to the fact that temperature is elemental to bacterial growth, there was thus a concerted effort by researchers to investigate the effects of temperature on biofilm formation. Albeit the numerous studies conducted in this area, none has examined the biofilm response to sudden temperature changes. Hence, this project aims to fill the void by subjecting biofilm to abrupt high temperature treatment. To achieve the objective of this work, a novel heating method for local temperature control in microfluidics; a small footprint temperature controller, was developed. This method regulates the local fluid temperature in the microfluidics via the controller and uses a syringe heater to heat up the microchannel. The enhanced flexibility, visibility and portability demonstrated in this design is a marked improvement from the previous heating technologies. Additionally, this work proposes an effortless approach to identify biofilm growth within microchannel via the confinement of biofilm culture in microfluidic channel; nutrient-zoning. This innovative method of limiting bacterial growth to a designated area within the microchannel allows for easy identification of biofilm formation by simply comparing the light intensity of the resultant zones. Results from this project proved that high temperatures can have detrimental effects in biofilm development, in particular the biofilm of Escherichia coli wherein, high temperature challenge can lead to cell death.